Pengaruh Motivasi dan Komunikasi Terhadap Kepuasan Kerja Serta Dampaknya Pada Kinerja Karyawan PT. Putra Mahkota Ganda Mekar - Wirda Nursanti; Nur Asih (Jurnal Manajemen FE-UB, 2020)
The data used in this study are primary data collected from respondents' answers based onthe questionnaire given, as many as 105 people. The data processing method uses the pathanalysis method with the help of SPSS version 22.0. Statistical testing using simultaneoussignificance test (F test), individual parameter significance test (t test) and Sobel Mediation Test.The results showed that simultaneously the motivation, communication and job satisfactionvariables had a significant effect on employee performance. Partially it shows that analysis 1: themotivation variable has a significant effect on employee performance, while analysis 2: thecommunication variable has a significant effect on employee performance and in analysis 3: thejob satisfaction variable has a significant effect on employee performance.Keywords: Motivation, Communication, Job Satisfaction and Employee Performance